Controllable growth of two-dimensional WSe2 using salt as co-solvent. Issue 40 (24th September 2018) - Wang, Xiangzhuo; Li, Yongkai; Zhuo, La; Zheng, Jingchuan; Peng, Xianglin; Jiao, Zefeng; Xiong, Xiaolu; Han, Junfeng; Xiao, Wende
Abstract : Various structures of two-dimensional (2D) WSe2 were controllably grown in a chemical vapor deposition (CVD) system. Abstract : Various structures of two-dimensional (2D) WSe2 were controllably grown in a chemical vapor deposition (CVD) system. Using salt as the co-solvent and surfactant, we were able to grow monolayer single-crystalline WSe2 flakes with lateral size of up to 215 μm and monolayer polycrystalline WSe2 with lateral size of a few millimeters on amorphous SiO2 substrates. Optical microscopy, atomic force microscopy, Raman spectra, photoluminescence spectra and X-ray photoelectron spectra measurements disclosed high quality of as-grown 2D WSe2 . Moreover, multilayer WSe2 flakes with spiral dislocations and uniform size were also achieved. Our study demonstrates that the salt-assisted CVD technique can be applied for the controllable synthesis of 2D transition metal dichalcogenides with various structures and morphologies, paving the way for developing novel catalysts and electronic devices.